Markedly raised synovial fluid leucocyte counts not associated with infectious arthritis in children. Issue 5 (October 1978) - Baldassare, A R; Chang, F; Zuckner, J
Abstract : Synovial fluid leucocyte counts greater than 50 000 cells/mm3 (50 X 10(9)/1) are usually associated with infectious arthritis. Six children, 3 of whom meet the criteria for juvenile rheumatoid arthritis (JRA), are described with synovial fluid white blood cell counts greater than 88 000 cells/mm3 (88 X 10(9)/1). Two had synovial fluid leucocyte counts greater than 100 000 cells/mm3 (100 X 10(9)/1). The diagnosis of infectious arthritis was unlikely in these 6 children since the synovial fluid smears and cultures for infectious agents were negative and their histories atypical for infection. While in most instances such markedly raised synovial fluid leucocyte counts indicate infection, this finding is not diagnostic of septic arthritis.